2021
DOI: 10.1093/arclin/acab006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Autism and Other Neurodevelopmental Disorders on Cognitive and Symptom Profiles: Considerations for Baseline Sport Concussion Assessment

Abstract: Objective The presence of neurodevelopmental disorders (ND) such as attention-deficit/hyperactivity disorder (ADHD) and learning disorders (LD) have demonstrated effects on Immediate Post-concussion Assessment and Cognitive Testing (ImPACT) performance. No current research has directly examined whether autism spectrum disorder (ASD) has similar effects. The current study compared ImPACT cognitive and symptom profiles in athletes with self-reported ASD to other NDs and healthy controls using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…These results provide further support that the symptom-reporting differences found between the clusters from baseline to postconcussion are likely the result of acute concussive effects rather than demographic or psychiatric history. Similarly, cognitive and symptom profiles have been reported to differ among athletes with neurodevelopmental conditions and those with history of concussion (Brooks et al, 2016; Cottle et al, 2017; Flood et al, 2020; Iverson et al, 2015; Maietta, Kuwabara, et al, 2021), and we did not find any differences between the clusters in neurodevelopmental diagnosis or history of concussion.…”
Section: Discussionsupporting
confidence: 67%
“…These results provide further support that the symptom-reporting differences found between the clusters from baseline to postconcussion are likely the result of acute concussive effects rather than demographic or psychiatric history. Similarly, cognitive and symptom profiles have been reported to differ among athletes with neurodevelopmental conditions and those with history of concussion (Brooks et al, 2016; Cottle et al, 2017; Flood et al, 2020; Iverson et al, 2015; Maietta, Kuwabara, et al, 2021), and we did not find any differences between the clusters in neurodevelopmental diagnosis or history of concussion.…”
Section: Discussionsupporting
confidence: 67%
“…There were 19 articles that investigated baseline cognitive performance and compared ADHD and/or LD groups to healthy athletes without self-reported neurodevelopmental diagnosis (see Table 1). Of these articles, 13 directly compared mean differences in performance on ImPACT Composite scores between ADHD and/or LD groups and healthy athletes (Biederman et al, 2015; Brooks et al, 2016; Cottle et al, 2017; Covassin et al, 2013; Elbin et al, 2013; Iaccarino et al, 2018; Kaye et al, 2019; Maietta, Kuwabara, et al, 2021; L. Manderino & Gunstad, 2018; Mautner et al, 2015; Peltonen et al, 2019; Salinas et al, 2016; Zuckerman et al, 2013), whereas five articles investigated additional aspects of baseline performance, for example, predictors of low performance (Brett, Solomon, et al, 2018; Brooks et al, 2018; Cook et al, 2017; Gardner et al, 2017; Houck et al, 2019) and one additional article utilized an experimental paradigm to assess ADHD effects on cognition post 10 soccer headings (Nowak et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…For the Reaction Time composite, the I 2 statistic indicated high levels of heterogeneity between studies and the Q statistic was significant. Maietta, Kuwabara, et al (2021) was identified as an influential outlier for Reaction Time, and so an updated meta-analysis was conducted using a random t distribution to reduce the effect of this study. The updated summary effect for Reaction Time was reduced from −0.62 to −0.35…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations